2022
DOI: 10.1038/s41598-022-13875-x
|View full text |Cite|
|
Sign up to set email alerts
|

Different bimodal neuromodulation settings reduce tinnitus symptoms in a large randomized trial

Abstract: More than 10% of the population suffers from tinnitus, which is a phantom auditory condition that is coded within the brain. A new neuromodulation approach to treat tinnitus has emerged that combines sound with electrical stimulation of somatosensory pathways, supported by multiple animal studies demonstrating that bimodal stimulation can elicit extensive neural plasticity within the auditory brain. More recently, in a large-scale clinical trial, bimodal neuromodulation combining sound and tongue stimulation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…The experimental group showed improvements in their TFI score that match or exceed previous research employing electric shocks on the tongue instead of vibrations on the wrist. Conlon et al (2020Conlon et al ( , 2022 found TFI improvements at week 12 between -10 and -15 points for three experimental groups, while Marks et al (2018) found an average TFI improvement of -8 points over 4 weeks. In comparison, our experimental group showed improvement of -14.3 for all participants, and -21.8 for those with moderate to severe tinnitus (baseline TFI score 50+).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The experimental group showed improvements in their TFI score that match or exceed previous research employing electric shocks on the tongue instead of vibrations on the wrist. Conlon et al (2020Conlon et al ( , 2022 found TFI improvements at week 12 between -10 and -15 points for three experimental groups, while Marks et al (2018) found an average TFI improvement of -8 points over 4 weeks. In comparison, our experimental group showed improvement of -14.3 for all participants, and -21.8 for those with moderate to severe tinnitus (baseline TFI score 50+).…”
Section: Discussionmentioning
confidence: 93%
“…The results of this study lay the framework for future research to investigate how different patterns and frequency ranges of tones affect the efficacy of treatment. Conlon et al (2022) showed that changing the parameter settings after 6 weeks of treatment allowed study participants to continue to make progress for an additional 6 weeks. This was an improvement on the findings of their prior study in which study participants experienced the greatest amount of progress in the first 6 weeks, but then plateaued for the final 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of bimodal auditory and central stimulation has already been investigated by combinations of acoustic stimulation/ sound therapies with transcranial direct current stimulation, likewise demonstrating inconclusive findings so far [53][54][55]. However, acoustic stimulation combined with stimulation of cranial nerves such as the vagus or the trigeminal nerve shows promising findings [56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%